THE CxP TYPOLOGY: A new understanding of normative deviance, gatekeeping, and community journalism. (2nd January 2016) - Funk, Marcus
Abstract : Structured interviews with community newspaper editors and publishers build on current theoretical understandings of normative deviance and gatekeeping theory. Editors and publishers encounter a great deal of audience interaction and a clear emphasis on news about "regular people and routine events, " which offers a topical rebuttal to gatekeeping theory's assertion that journalists are attracted to news about conflict and celebrity due to a lack of dialogue with media consumers. A deeper reading of the text, however, demonstrates that "regular people" and "routine events" remain rooted in conflict and celebrity. This study suggests a theoretical broadening of normative deviance and a new model, the "CxP Typology, " to aid the theoretical expression of normative deviance.